Systematic review: risk sexual behavior, sexually transmitted infections, and adolescent pregnancy prevention interventions - Elviera Gamelia; Anies Anies; Bagoes Widjanarko; Zahroh Shaluhiyah (AOSIS, 2023)
In many countries, there is a high number of teenage pregnancies, Sexually Transmitted Infections (STIs), and unsafe sexual behavior, so there is a need for adolescent health intervention programs to change behavior. The effectiveness of comprehensive interventions in various contexts to reduce teenage pregnancy, STIs, and related sexual risk behaviors is reviewed in this system‑ atic. This study aimed to identify risk sexual behavior, sexually transmitted infections, and adolescent pregnancy prevention interventions. Literature search strategy from January 2008 to December 2022 through electronic databases. Key words 'teenage prenancy' OR 'teen preg‑ nancy' OR 'pregnancy adolescence', AND 'maternal education', AND 'randomised clinical trial', AND 'risk behavior'. Articles that were deemed worthy of following the PRISMA guidelines were 28 articles. Most studies looked at school‑based, individual, community, clinic, and family‑based care. Most studies were followed up after intervention at intervals from one month to seven years, and the majority of the population and sample were adolescents with ages ranging from 13 to 18 years. Implementation of research in urban, suburban, and rural areas. This program has proven successful in preventing pregnancy, contracep‑ tive use, STI and HIV, sexual behavior, dropping out of school, knowledge about pregnancy, sexuality, attitudes towards sexuality, intention to change risky sexual behavior, self‑efficacy, and increasing parent‑children. This article describes some basic trends in adolescent pregnancy preven‑ tion interventions in several countries that can be used as a reference for health programs. Unproven effectiveness can be implemented in conjunction with other interventions that have a high‑quality impact.